Edukasi Pemanfaatan Daun Salam dan Kencur Kaitannya dengan Imunitas pada Lansia Serta Sebagai Insektisida Alami di Posyandu Beringin V Kelurahan Kedungwuni Barat - Fitrianingsih Fitrianingsih; Izza Ratna Kumala (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Herbal plants or often known as TOGA family medicinal plants are very diverse, the benefits of this family of medicinal plants are very diverse, ranging from curing flu to other serious illnesses. In life from ancient times until now, there are known methods of treatment, both chemical and herbal/traditional. Bay leaf is a plant with the Latin name Syzygium polyanthum which is one of the herbs most often used in traditional Indonesian cooking. Not only delicious food, the benefits of bay leaves also penetrate the world of health and beauty in the form of leaf decoction and bay leaf extract. Bay leaf extract also has benefits as a natural insecticide. One way to improve the body's immune system is by consuming substances or substances that are immunomodulatory. Immunomodulators are substances or drugs that can modulate the function and activity of the immune system. Immunomodulators can be obtained from traditional medicinal plants, such as turmeric, ginger and galangal. These three plants are native to Indonesia and have been used for generations to relieve various diseases. The aim of this community service activity is to provide education to elderly people about the use of bay leaves and galangal in relation to immunity and natural insecticides at Posyandu Beringin V, West Kedungwuni District.